Improving the Awareness of Stakeholders on Anti-Bullying Through Advocacy Campaign - Garcia, Eddie Florentino (JPAIR Institutional Research, 2020)
Knowing the benefits of implementing the Anti-Bullying Law in the country, and the Advocacy Campaign on Anti-bullying was implemented to address the bullying problems in Sta. Justina High School. The descriptive method was employed in discussing the responses. This is community outreach and impactconfined to the assessment of the Level of Awareness on Anti-Bullying Law of the selected stakeholders of Sta. Justina High School. Findings revealed that the level of awareness of stakeholders on anti-bullying, the adoption of the anti-bullying policy, and mechanisms to address bullying were aware before implementing the intervention. The implementation of the Advocacy Campaign was Highly Implemented, and the level of acceptance of the strategies was highly accepted. The advocacy campaign was very effective and improved the awareness of the stakeholders after its implementation. Furthermore, the acts of bullying, adoption of anti-bullying policies, the mechanism to address bullying, problems encountered on anti-bullying, level of implementation, and acceptance of the strategies and activities implemented have a significant relationship to the level of awareness stakeholders anti-bullying. Therefore, it is recommended that the Advocacy Campaign on Anti-Bullying be institutionalized in other schools in Schools Division Office (SDO) Camarines Sur to combat bullying in schools. This was funded under the Basic Education Research Fund (BERF) through the Division Research Committee and PPRD Region V.
Keywords: community outreach and impact; bullying; anti-bullying; advocacy campaign; descriptive method; Philippines